FCMpy: A Python Module for Constructing and Analyzing Fuzzy Cognitive Maps - Mkhitaryan, Samvel; Giabbanelli, Philippe J; Wozniak, Maciej K; Napoles, Gonzalo; de Vries, Nanne K; Crutzen, Rik (arXiv.org, 2021)
FCMpy is an open source package in Python for building and analyzing Fuzzy Cognitive Maps. More specifically, the package allows 1) deriving fuzzy causal weights from qualitative data, 2) simulating the system behavior, 3) applying machine learning algorithms (e.g., Nonlinear Hebbian Learning, Active Hebbian Learning, Genetic Algorithms and Deterministic Learning) to adjust the FCM causal weight matrix and to solve classification problems, and 4) implementing scenario analysis by simulating hypothetical interventions (i.e., analyzing what-if scenarios).